2014
DOI: 10.1111/cns.12319
|View full text |Cite
|
Sign up to set email alerts
|

To Sleep or Not to Sleep: A Repeated Daily Challenge for African American Children

Abstract: At nighttime children habitually obtained few hours of sleep with diurnal sleep fluctuations likely being "a need" and "a chance." Interventions might emphasize on creating optimal opportunities to sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Preschoolers with a late bedtime have greater onset IIV and waking IIV than other preschoolers [63]. School-aged children have greater duration IIV on weekends than weekdays, but greater waking variability on weekdays than weekends [77]. Similar, adolescents have greater onset IIV and waking IIV during vacation periods than school periods [59], and greater duration IIV is likewise associated with a larger difference between weekday and weekend sleep duration [33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preschoolers with a late bedtime have greater onset IIV and waking IIV than other preschoolers [63]. School-aged children have greater duration IIV on weekends than weekdays, but greater waking variability on weekdays than weekends [77]. Similar, adolescents have greater onset IIV and waking IIV during vacation periods than school periods [59], and greater duration IIV is likewise associated with a larger difference between weekday and weekend sleep duration [33].…”
Section: Resultsmentioning
confidence: 99%
“…However, the time of day when sleepiness is assessed may be important when examining associations with sleep IIV: Spruyt et al [31] found that sleepiness rated early in the day was unassociated with duration IIV or onset IIV whereas sleepiness rated in the afternoon was associated with multiple sleep domains including greater onset IIV and greater duration IIV. There does appear to be an association between napping and greater onset IIV, waking IIV, and duration IIV [36,77]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing evidence that poor quality and insufficient sleep has a negative impact on infants, children, and mothers (Hall et al, ; Havekes et al, ; Holley et al, ; Spruyt et al, ). The findings from this study show that sleep behaviours and patterns of sleep are at least a small problem for almost one third (30.6%) of mothers of 9‐month‐old infants, one in four mothers (21.4%) of 3‐year‐olds, and more than one in 10 (11.9%) mothers of 5‐year‐old children.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of sleep on the health and well‐being of infants, children, and their carers is acknowledged as an important public health issue (Spruyt, Alaribe, & Newbara, ). Poor sleep patterns have been linked with poorer cognition and memory loss in adults (Havekes, Vecsey, & Abel, ).…”
Section: Introductionmentioning
confidence: 99%